Design Characteristics of Healing Garden for down’s Syndrome Children in Malaysia - A. Shukor, Shureen Faris (2007)
Healing landscapes have always been associated with studying and planning for a specific type of population. Therefore, this study was carried out in order to identify the design characteristics of healing gardens for the Down’s syndrome children in Malaysia. The behavior and disabilities of children with the Down’s syndrome were studied together with the level of awareness and preferences of their parents towards healing garden. These will later determine the design characters in the healing garden that could contribute towards the wellbeing of the children. A total of 58 parents with children who have Down’s syndrome and registered with the Malaysian Society of Down’s Syndrome aged between 1 to 12 years old were involved in the study. Close and open- ended questionnaires with lists of landscape characters for the parents to rate were based on recommendations and guidelines for healing gardens from past studies. The parents had to identify the activities and the landscape design characters that their children most preferred when in a garden. Behavioral observation was also carried out to support this. Results from the findings have shown that for the Down’s syndrome patients who are mostly affected by sensory deficits such as hearing and visual impairment, difficulty in speech and delay in socialization, the healing garden should offer facilities that could encourage a sense of security, space for interaction and easy supervision. It should also heighten their sensory awareness and experience. The design considerations were listed into four groups that consist of the garden layout, spaces, hardscape and softscape characters based from the preferences of the parents. The result suggests that the healing garden should be considered as part of an early intervention and as a part of an out door therapy programme for children with Down’s syndrome.